Quaker Constitutionalism and the Political Thought of John Dickinson - Calvert, Jane E (Cambridge University Press, 2013)
This study has three overarching purposes – to describe Quaker constitutional theory; to identify the practical expressions of this theory; and to explain the thought and action of Founding Father John Dickinson within this tradition, using him as the best, though imperfect exemplar of it in early America.